A profile of dementia patients in a Serbian sample – experience from the center for dementia and memory disorders - Salak-Djokić, Biljana; Stojković, Tanja; Mandić-Stojmenović, Gorana; Stefanova, Elka (Vojnosanitetski pregled, 2021)
Background/Aim. In accordance with modern trends of organizing specialized service dealing with dementia, the first memory clinic in Serbia – Center for memory disorders and dementia was established in 2008 in Belgrade at Neurology Clinic – Clinical Center of Serbia (CCS) as a university-affiliated outpatient clinic for subjects with cognitive impairment and dementia. The aim of this report was to outline the frequency of diagnosis, sociodemographic and medical characteristics of patients referring to the Center for memory disorders and dementia. Methods. The sample consisted of patients registered between 2008 and 2016 who underwent comprehensive and specialized diagnostic procedures in the Center. Results. A total of 3,873 visits were made for 2,198 patients, 39.6% of which proceed to annually follow-up visits. The majority of the sample (65.3%) was women. The mean age was 69.8 ± 12.1 years (range 29–89 years) and the average education level was 12.1 ± 3.3 years. Of this total number, at the moment of the first visit, 44.4% of the patients were fulfill criteria for Mild cognitive impairment (MCI), 28.2% had dementia due to Alzheimer’s disease (AD), 7.8% had dementia secondary to a vascular pathology (VaD), 7.3% had frontotemporal dementia (FTD), 0.6% had dementia with Lewy bodies (DLB), and 1.7% had dementia due to Parkinson's disease (PDD). The mean Mini Mental test score in the whole sample was 22.6 ± 6.8 points. Conclusion. The data collected through the activity of the Center enabled an insight into the demographic and medical characteristics of patients, as well as planning further activities in the health care system. The systemic introduction of more standardized diagnostic practices, establishing and networking of similar centers will improve the accuracy and rate of dementia diagnosis in the Serbian population.
Keywords: dementia; memory disorders; serbia; demography; neuropsychological tests; sensitivity and specificity